Knowing Letter Through Media Flash Card Children Aged 4-5 Years - Setyaningrum Setyaningrum; Zulkarnaen Zulkarnaen (JURNAL INDRIA (Jurnal Ilmiah Pendidikan Prasekolah dan Sekolah Awal), 2023)
This research aimed to improve the ability to recognize letters through flashcards in children aged 4-5 years. This study used a qualitative method with Classroom Action Research. The research was conducted at TK Bustanul Athfal Aisyiyah Karangasem with a total of 20 children as subjects. Data collection was done through observation, interviews, and documentation. The results showed that children better understand learning by using interesting media such as flashcards. By using flashcards, children can understand letters in bright colors and are easy to understand. Varied learning makes children enthusiastic and motivated to improve their ability to understand and recognize letters.